Kebiasaan Ibu untuk cuci tangan dan kejadian diare anak; Studi korelasi di Desa Muara Badak Ilir Kecamatan Muara Badak Kabupaten Kutai Kartanegara tahun 2015 - Rahmawati Rifai; Abdul Wahab; Yayi Suryo Prabandari (Berita Kedokteran Masyarakat (BKM), 2016)
Mothers’ hand-washing habits and incidence of diarrhea among their children: a community study in Kutai KartanegaraPurposeThis study aimed to explore the relationship between mothers’ handwashing with children’s diarrhea in Muara Badak Ilir Village, Muara Badak District, Kutai Kartanegara Regency. MethodsSixty-one mothers residing in Muara Badak Ilir village who have children aged 7-24 months were interviewed with questionnaires and guidelines. Data were analyzed using univariable, bivariable with chi square tests and multivariable analysis. ResultsThere were 43 respondents who were not used to washing their hands with soap, while, children aged 7-24 months who had diarrhea in the last 2 months were 39 children. Respondents who did not wash their hands with soap were 6.6 times more likely to experience diarrhea compared with respondents who wash their hands with soap.ConclusionThere was a correlation between mothers’ hand-washing habit and incidence of diarrhea among children in Kutai Kartanegara. Primary health care workers are expected to be more active in providing information about diarrhea and how to do hand-washing properly. This study recommends to increase the role of primary health workers through training and coaching in order to become better health promoters in each region.